Highly penetrative liposome nanomedicine generated by a biomimetic strategy for enhanced cancer chemotherapy. (25th April 2018) - Jia, Yali; Sheng, Zonghai; Hu, Dehong; Yan, Fei; Zhu, Mingting; Gao, Guanhui; Wang, Pan; Liu, Xin; Wang, Xiaobing; Zheng, Hairong
Abstract : Biomimetic liposome nanomedicine with deep tumor penetration and specific homotypic targeting ability enhanced cancer chemotherapy. Abstract : Liposome nanomedicine has been successfully applied for cancer chemotherapy in patients. However, in general, the therapeutic efficacy is confined by its limited accumulation and penetration in solid tumors. Here, we established a biomimetic strategy for the preparation of highly penetrative liposome nanomedicine for enhanced chemotherapeutic efficacy. By applying this unique type of nanomedicine, membrane proteins on the cancer cells are used as highly penetrative targeting ligands. Biomimetic liposomes are highly stable, exhibiting a superior in vitro homologous targeting ability, and a 2.25-fold deeper penetration in 3D tumor spheroids when compared to conventional liposome nanomedicine. The fluorescence/photoacoustic dual-modal imaging approach demonstrated enhanced tumor accumulation and improved tumor penetration of the biomimetic liposome in C6 glioma tumor-bearing nude mice. Following the intravenous administration of biomimetic liposome nanomedicine, the tumor inhibition rate reached up to 93.3%, which was significantly higher when compared to that of conventional liposome nanomedicine (69.3%). Moreover, histopathological analyses demonstrated that biomimetic liposome nanomedicine has limited side effects. Therefore, these results suggested that a cancer cell membrane-based biomimetic strategy may provide a breakthrough approach for enhancing drug penetration and improving treatment efficacy, holding a great promise for further clinical studies.